?Anglicismo o la forma adaptada al espanol? Una mirada al léxico de las redes sociales a través del CORPES XXI - Arribas González, Laura (Verba hispanica, 2025)
Social networks are digital platforms with millions of users and a highly distinctive lexicon. The aim of this paper is to analyse the degree of adaptation into Spanish of a set of anglicisms related to social networks and, subsequently, to determine which of the two forms – original or adapted – has a stronger documentary presence in texts published in Spain between 2020 and 2025, according to CORPES XXI. This analysis will also help define and characterize the corpus of texts in which these forms appear.
Keywords: adaptación; adaptation; anglicismos; anglicisms; anglicizmi; corpus; družbena omrežja; espanol; korpus; prilagoditev; redes sociales; social networks; Spanish; španščina